In Search of Commonly Used Language Learning Strategies by EFL students - MASBIROROTNI MASBIROROTNI; NUNUNG FAJARYANI (Universitas Jambi, Indonesia, 2020)
Language learning strategy is one of the factors that can contribute to the success in learning a foreign language including for Indonesian students. The purpose of this current study was to examine the learning strategies of English as foreign language students in one state university in Jambi Province. This current study used a survey approach to deal with the issue of the learning strategies of English as foreign language students. Data were collected through using the Language Learning Strategy Questionnaire (LLSQ). The participants of this study consisted of 129 students. Overall, the findings revealed that cognitive and meta-cognitive strategies were most commonly used by students in speaking, reading, and writing skills. However, cognitive and social strategies were the most frequently used by students for listening skill. Suggestions and future studies are also discussed.